A guide to ancient Greek drama - Storey, Ian Christopher 1946-; Allan, Arlene (Blackwell guides to classical literature, 2014)
This edition features wide-ranging, systematically organized scholarship in a concise introduction to ancient Greek drama, which flourished from the sixth to third century BC. It covers all three genres of ancient Greek drama: tragedy, comedy, and satyr-drama. It also surveys the extant work of Aeschylus, Sophokles, Euripides, Aristophanes, and Menander, and includes entries on lost playwrights. This book examines contextual issues such as the origins of dramatic art forms ; the conventions of the festivals and the theater ; drama's relationship with the worship of Dionysos ; political dimensions of drama and how to read and watch Greek drama. It also includes single-page synopses of every surviving ancient Greek play.